Dalila Silk House: Dalila mask by agent zieyfa / Nornazifa Mohamad Zulkifli - Mohamad Zulkifli, Nornazifa (2021)
A business is an organization that people make and sell goods or services. In other words, business is a platform for earning profits and selling products and services that use a lot of effort and individual activities to make it a success. In this case, a business needs proper planning that could make the owner reach business milestones. In addition, it can be done through a business plan that has its key elements to improve the plan and make it easier to make decisions. There were seven essential points in marketing that we should pay particular attention to. First and foremost, channel management. After that, there's marketing data management, a marketing strategy, pricing, product service management, promotion, and finally selling. Moreover, this job is assisting me in learning a great deal about online marketing. From the very beginning to the very end. First, I must consider what I need to sell, after which I must build my own personal Facebook page and begin the process of setting things up. After then, a company must register with e-commerce in order to keep track of all of its data.Furthermore, we must have a solid marketing strategy and plan in place to ensure that our business runs well and that people or consumers are interested in it.